(untitled) - Horby, A. S. (Oxford, 1995)
This updated edition, in addition to a wide lexical coverage, an abundance of useful examples, and detailed information on grammar and usage, offers a number of new features which makes the dictionary even more authoritative and helpful to users. These include: use of the unparalleled information contained in the British National Corpus of Spoken and Written British and American English; a simple defining style, restricted to a carefully-chosen vocabulary of 2800 common words; and 16 language study pages, covering important aspects of English such as verbs, nouns, and vocabulary.
Keywords: English language,Tiếng Anh; Dictionaries,Từ điển